Single amino acid change in tomato brown rugose fruit virus breaks virus-specific resistance in new resistant tomato cultivar - Zisi, Zafeiro; Ghijselings, Lucas; Vogel, Elise; Vos, Christine; Matthijnssens, Jelle (Frontiers in Plant Science, 2024)
Tomato cultivation across the world is severely affected by emerging plant viruses. An effective method for protection of commercial crops against viral threats is the use of cultivars harboring resistance genes. Tomato brown rugose fruit virus (ToBRFV), a recently emerged tobamovirus, is able to overcome the dominant Tm-2 2 resistance that is present in the majority of commercial tomato cultivars. In an effort to alleviate the severe consequences of ToBRFV on tomato production, tomato breeding companies are developing new cultivars with varying levels of resistance against ToBRFV. In the present study, cultivars with a new resistant phenotype against ToBRFV were screened against a wild type isolate of ToBRFV and subsequently their performance under commercial greenhouses conditions was monitored. Following the identification of ToBRFV symptoms in a commercial greenhouse -where both new resistant and susceptible cultivars were interplanted - these cultivars were more closely examined. The presence of ToBRFV was molecularly confirmed on both cultivar types, suggesting that the new resistance had been broken. High throughput sequencing was used to study the complete genomes of viral isolates present in the two cultivar types. The analysis revealed a single amino acid change at position 82 of the movement protein of ToBRFV in the isolate present in the new resistant cultivar compared with the isolate identified in the susceptible cultivar. A screening bioassay, that was performed to compare the infectivity of the two ToBRFV isolates, confirmed that only the isolate with this specific amino acid change could successfully infect the resistant cultivar, overcoming the new resistance against ToBRFV.